Pengaruh Engine Bleed Trip Terhadap Tingkat Kebutuhan Pergantian Komponen Pada Pesawat B737-800 - Nova, Muhammad Andi; Iradhat, Achmad Yudha; Siregar, James; Dzulfiqar, Mohamad Alif; Dija, Nur Rafia; Rossbandrio, Wowo (Jurnal Teknologi dan Riset Terapan (JATRA), 2024)
An engine bleed trip is an indication that there is a failure in the engine bleed system in regulating the temperature and pressure of the bleed air. This can affect the work of other systems that rely on the output of the engine bleed system, one of which is the cabin pressure system. The aim of this research is to find out the percentage level of the need for main components in the engine bleed system to be replaced in handling engine bleed trip cases. This research is an ex post-facto comparative research with primary data collection methods sourced from aircraft maintenance databases and interviews. The research results showed that from a total of 52 bleed trip cases that occurred during 17 months, the percentage of main components that needed to be replaced were the 390F thermostat sensor (42.3%), precooler control valve (19.2%), pressure regulating shuttle valve (11 .5%), bleed air regulator (7.7%), and the rest are other components.